Theoretical stress–strain model for circular concrete columns confined by GFRP spirals and hoops. (1st November 2015) - Afifi, Mohammad Z.; Mohamed, Hamdy M.; Benmokrane, Brahim
Highlights: This paper provides a basis for theoretical stress–strain behavior of GFRP RC columns. Confinement models were proposed to predict the maximum concrete stress and strain. New design equations were introduced to predict the stress–strain responses. Abstract: Fiber-reinforced polymer (FRP) bars have emerged as an effective alternative for providing shear and flexural reinforcement for reinforced concrete (RC) members in different applications. Nonetheless, the axial compression behavior of circular FRP RC columns has not yet been defined. Due to the differences in the mechanical properties of FRP and steel reinforcement, the compression behavior of concrete columns reinforced with FRP reinforcement may differ from those reinforced with steel. This study proposed a confinement model to predict the axial stress–strain behavior of RC columns reinforced with glass-FRP (GFRP) bars in longitudinal direction and confined by GFRP spirals or hoops. The model takes into account the effect of many parameters related to transverse reinforcement configuration, longitudinal reinforcement ratio, and volumetric ratio. The proposed model can be used to calculate the confining pressure, confined concrete core stress, corresponding concrete strain, and stress–strain relationship. The analytical stress–strain relationships were compared with experimental database of circular concrete columns reinforced with GFRP bars, spirals, and hoops. The proposed equations demonstrated good ability in predicting the stress–strain behavior of the tested GFRP RC column specimens.